2020
DOI: 10.1186/s12913-020-4911-6
|View full text |Cite
|
Sign up to set email alerts
|

Supporting the clinical use of the ICF in Japan – development of the Japanese version of the simple, intuitive descriptions for the ICF Generic-30 set, its operationalization through a rating reference guide, and interrater reliability study

Abstract: Background: The World Health Organization developed the International Classification of Functioning, Disability, and Health (ICF) in 2001 and has been in the process of implementing it in clinics since then. Current international efforts to implement ICF in rehabilitation clinics include the implementation of ICF Core Sets and the development of simple, intuitive descriptions for the ICF Generic-30 Set (also called Rehabilitation Set). The present study was designed to operationalize these ICF tools for clinic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 28 publications
0
35
0
Order By: Relevance
“…The pre-implementation retrospective audit showed that the majority of clinical concepts documented in the discharge summaries were directly or partially linked to the mPSC items. The World Health Organization (WHO) ICF ClinFIT set has exhaustive categories, in the “body function” and “activity and participation” domains ( 32 ), which describe patients’ functional status comprehensively in inpatient rehabilitation settings and across the continuum of care ( 33 ). Furthermore, it was sensitive to change over time, generating an interval score (EI) (from admission to discharge and 3-month post-discharge), which provided information on various aspects of function and disability.…”
Section: Discussionmentioning
confidence: 99%
“…The pre-implementation retrospective audit showed that the majority of clinical concepts documented in the discharge summaries were directly or partially linked to the mPSC items. The World Health Organization (WHO) ICF ClinFIT set has exhaustive categories, in the “body function” and “activity and participation” domains ( 32 ), which describe patients’ functional status comprehensively in inpatient rehabilitation settings and across the continuum of care ( 33 ). Furthermore, it was sensitive to change over time, generating an interval score (EI) (from admission to discharge and 3-month post-discharge), which provided information on various aspects of function and disability.…”
Section: Discussionmentioning
confidence: 99%
“…The development of the reference guide (in combination with the guide described by Mukaino et al which was for activity and participation categories) [ 14 ] has resulted in the completion of the reference guide for all items in the ICF Generic-30 set. This development will support the clinical use of the ICF Generic-30 set and foster its clinical implementation.…”
Section: Discussionmentioning
confidence: 99%
“…The terms “acute”, “subacute”, and “chronic” mentioned above indicate time periods within 14 days, 15 to 120 days, and more than 120 days after onset of the disease, respectively. The Japanese version of the simple, intuitive descriptions of the ICF Generic-30 Set [ 14 ] was used to facilitate the understanding of the category, which also supported the determination of the ratings. The Japanese-language simple, intuitive descriptions of the ICF Generic-30 Set were developed based on an established consensus process that has been promoted by national physical and rehabilitation medicine societies worldwide [ 11 , 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though, ICF Core Sets assist the process of defining what to assess, ICF categories alone are not operational items and may thus be difficult to assess and use in everyday clinical practice. Consequently, further specification of ICF categories in a user-friendly language is required to promote the use of ICF in daily clinical practice (30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%